Jejak Spiritualitas Islam dalam Konstruksi Etika Akuntan Publik - Ida Ayu Nursanty; Baiq Anggun Hilendri Lestari; Rosyia Wardani; Lalu Takdir Jumaidi; Baiq Desthania Prathama (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study aims to construct the ethics of public accountants from the perspective of Islamic spirituality. Using a spiritualist paradigm and a spiritualist research design, the study seeks to develop an ethical concept grounded in Islamic spirituality. Through zikr (remembrance of God), prayer, and contemplation methods, the researcher attained balance of intellect, justice, honesty, and love as instruments for data analysis. The findings reveal that the balance of intellect, justice, honesty, and love—reflected in the personality of public accountants—guides them toward humanistic values, fulfilling their role as khalifah (vicegerents) on earth. Ethical public accountants not only uphold professional trust but also spread love toward humanity and nature while nurturing spiritual awareness—an awareness of obedience to the will of God. For humankind, spiritual awareness is a divine instrument used to connect, unite, and return to God—this being the ultimate purpose of human life.